1987
DOI: 10.1080/03079458708436399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the haemagglutination inhibition test and the serum neutralisation test in tracheal organ cultures for typing infectious bronchitis virus strains

Abstract: SUMMARYFive strains of infectious bronchitis (IB) virus, which had been compared antigenically by the serum neutralisation (SN) test in tracheal organ cultures (OC), were arbitarily coded and then compared by the haemagglutination inhibition (HI) test. Their antigenic relationships were found to be similar by the two methods but, because of the high and variable cross reactions found in the HI test, the differences between the strains were less clear by that method. It was concluded that the HI test, in its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This cross-reactivity of chicken serum stems from the fact that many epitopes on the IBV structural proteins (with the exception of the serotype-specific epitopes on the SI protein) are shared by different serotypes (Koch, et al, 1986;Niesters et al, 1987;Ignjatovic & McWaters, 1991;Karaca et al, 1992). Therefore, IBV antibodies induced by exposure to one serotype tend to cross-react with other IBV serotypes in most assays except the VN test (Lucio & Hitchner 1970;Hopkins, 1974;Johnson & Marquardt 1975;Marquardt et al, 1981;Cook et al, 1987;. The C-ELJSA described here circumvents the cross reactivity problem associated with chicken sera.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-reactivity of chicken serum stems from the fact that many epitopes on the IBV structural proteins (with the exception of the serotype-specific epitopes on the SI protein) are shared by different serotypes (Koch, et al, 1986;Niesters et al, 1987;Ignjatovic & McWaters, 1991;Karaca et al, 1992). Therefore, IBV antibodies induced by exposure to one serotype tend to cross-react with other IBV serotypes in most assays except the VN test (Lucio & Hitchner 1970;Hopkins, 1974;Johnson & Marquardt 1975;Marquardt et al, 1981;Cook et al, 1987;. The C-ELJSA described here circumvents the cross reactivity problem associated with chicken sera.…”
Section: Discussionmentioning
confidence: 99%
“…Brown & Bracewell (1985) found high cross-reactions between serotypes in the HI test. Cook et al (1987) showed that the antigenic relationships of strains when serotyping by VNT (using TOCs) and HI test was similar but, because of the high and variable cross-reactions found in the HI test, the differences between the strains were less clear in the HI test.…”
Section: Antigenic Typesmentioning
confidence: 99%
“…There are several reports on serotyping by the HI test (Lashgari & Newman, 1984;Brown & Bracewell, 1985;Toro et al, 1987;Cook et al, 1987;Capua et al, 1998Capua et al, , 1999. Brown & Bracewell (1985) found high cross-reactions between serotypes in the HI test.…”
Section: Antigenic Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotypes and genotypes are usually used to character IBV strains. Traditionally, VN and HI tests were used to differentiate and classify IBV strains [13,14], and monoclonal antibodies have been developed against several serotypes of IBV [15][16][17], although serotype-specific monoclonal antibodies are only available for a small number of serotypes. In recent researches, S1 gene sequencing and subsequent genetic analysis have provided a fast and accurate method for classifying and predicting IBVs [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%